Laundry Business Strategy to Increase Revenue (Case: Sosor Laundry) - Lydia Indriana Cristianty; Harimukti Wandebori (Syntax Corporation, 2025)
The laundry service sector in East Jakarta, especially in the Condet region, has undergone substantial expansion owing to the rising demand for convenient, high-quality laundry services among busy professionals, families, and students. Sosor Laundry, founded in 2019, has developed into a distinguished laundry service with five locations in East Jakarta. Recent challenges, including heightened competition, increasing operational expenses, and stagnating income, have underscored the necessity for a comprehensive strategy to secure sustained development and profitability. This study seeks to formulate a growth strategy for Sosor Laundry through an analysis of its internal and external analysis. The study employs Porter's Five Forces, and an extensive Value Chain Analysis to ascertain Sosor Laundry's principal strengths, weaknesses, opportunities, and threats. The study analyzes market analysis, competition analysis, and market trends to develop an effective strategy plan. The results indicate that Sosor Laundry's competitive edge is derived from its superior service quality, specialized care for delicate fabrics and carpets, and complimentary pickup and delivery services. The report offers essential ways to enhance market position, including service innovation, operational efficiency, targeted marketing efforts, and geographic expansion. A phased implementation strategy is outlined, anticipating a revenue gain of 30-40% within the forthcoming year. This study suggests that Sosor Laundry can mitigate competitive pressures and attain long-term growth and profitability in the highly competitive laundry sector of East Jakarta by enhancing service differentiation, forming strategic partnerships, and implementing sustainable practices.